Sexual orientation and labor market outcomes - Nick Drydakis (IZA World of Labor, 2014)
Studies from countries with laws against discrimination on the basis of sexual orientation suggest that gay and lesbian employees report more incidents of harassment and are more likely to report experiencing unfair treatment in the labor market than are heterosexual employees. Gay men are found to earn less than comparably skilled and experienced heterosexual men. For lesbians, the patterns are ambiguous: in some countries they have been found to earn less than their heterosexual counterparts, while in others they earn the same or more. Both gay men and lesbians tend to be less satisfied with their jobs than their heterosexual counterparts.
Keywords: J7; J16; J31; J42; J64; J71; J82; 330; sexual orientation; access to vacancies; earnings; job satisfaction; bullying